(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of this article is to discuss the correlation between micro, small and medium enterprises and the number of unemployment in Białogard and Świdwin districts. The study covered the years 2010-2015. The data come from the Local Data Bank of CSO. Pearson correlation analysis was performed. The relationship between the percentage of SMEs (micro, small and medium-sized units) and the size of registered unemployment have been examined for both districts. The strength of the correlation between the SME sector and the size of registered unemployment was a mild in the case of micro and small enterprises and poor in the case of medium-sized enterprises.